2006
DOI: 10.1111/j.1365-2788.2006.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of marital quality to the well‐being of parents of children with developmental disabilities

Abstract: The findings support the importance of the marital relationship to parental well-being and illustrate the value of including fathers in studies of children with developmental disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
172
1
24

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(209 citation statements)
references
References 52 publications
12
172
1
24
Order By: Relevance
“…In current study, it is evidenced that quality marital relationship had significant impact on psychosocial life of caregivers. These findings are in line with the previous findings demonstrating satisfaction with social support and marital quality [19][20][21] Study findings also evident that caring for a stroke survivors for a very long time had negative impact on environmental quality of life aspects. Findings found agreement in a previous study conducted by Ogunlana et al [22] which reported that duration of stroke had worse impact on quality of life in caregivers.…”
Section: Discussionsupporting
confidence: 92%
“…In current study, it is evidenced that quality marital relationship had significant impact on psychosocial life of caregivers. These findings are in line with the previous findings demonstrating satisfaction with social support and marital quality [19][20][21] Study findings also evident that caring for a stroke survivors for a very long time had negative impact on environmental quality of life aspects. Findings found agreement in a previous study conducted by Ogunlana et al [22] which reported that duration of stroke had worse impact on quality of life in caregivers.…”
Section: Discussionsupporting
confidence: 92%
“…When mothers notice that their husbands or partners participate in caring for their disabled child, the quality of marriage tends to improve (Hallberg, 2014). It is worth noting that marital relationship quality is related to parental well-being (Kersh, Hedvat, Hauser-Cram, & Warfield, 2006). Baucom, Shoham, Mueser, Daiuto, and Sticker (1998) indicate that there is a need for further research on the marital relationship and the psychological well-being of parents in families of children with disabilities, not only because of the deficit of such studies, but also by virtue of the importance of this relationship in creating and maintaining proper relationships between members of these families.…”
mentioning
confidence: 99%
“…Wachtel e Carter 15 Mães que receberam intervenção apresentaram maior aceitação do diagnóstico de seus filhos e estilo de parentalidade mais positivo. Kersh et al 16 Os pais com maior qualidade marital apresentavam menos estresse e menos sintomas depressivos. Mickelson et al 17 Os pais que atribuíram a condição da criança à própria culpa e ao ambiente apresentaram um pior ajustamento (autismo).…”
Section: Discussionunclassified
“…Neste caso, o suporte social e a escolaridade foram fatores mediadores do estresse materno e favoreceram o ajustamento familiar como um todo 10,11 . Os estudos apontam que baixos níveis de suporte social são os preditores mais fortes para depressão e ansiedade, 8,13,16 que a diminuição dos escores de depressão estão relacionados a intervenções que oferecem apoio social 12,14 e, por fim, que a intervenção mais adequada no contexto do autismo depende da fase de desenvolvimento em que a criança está, bem como do contexto familiar. 7 Por outro lado, estudos revelam que mães que vivem situações semelhantes, como o fato de ter um filho com desenvolvimento atípico, nem sempre são afetadas da mesma maneira, ainda que estejam diante desta sobrecarga 5 .…”
Section: Discussionunclassified